PENGARUH RELATIONSHIP MARKETING TERHADAP LOYALITAS NASABAH DI PT.BANK MANDIRI KC.DOTULOLONG LASUT MANADO - KANDOU, HAJAR ASWAT; KALANGI, Johny A. F.; ROGAHANG, JOULA J. (JURNAL ADMINISTRASI BISNIS, 2017)
At Bank Mandiri KC.Dululolong Lasut Manado experienced the problem of unstable customer savings rate. This unstable number of subscribers is biased by the downturn in the client's economic condition, or there are other factors between services that do not correspond to unsatisfactory interests or unsatisfactory facilities that customers turn to other banks. Planting the credibility of the company, certainly not an easy thing, it takes an appropriate strategy for the purpose and objectives can be achieved optimally, especially in the field of marketing. Basically Relationship marketing is a long-term relationship and bond between producers, consumers, suppliers, and other actors. Customer loyalty is a behavior associated with a product's brand, including possible renewal of a contract in the future. This research uses quantitative method, sampling technique in this study using Simple Random Sampling, The formula used in calculating this simple correlation coefficient is product moment. From the results of statistical testing can be seen clearly that the free variable Relationship Marketing affect the dependent variable Customer Loyalty. the influence of the given free variable is positive which means the more active relationship marketing then result in higher loyalty of customers generated. These results are also in accordance with the proposed hypothesis. This shows that relationship marketing is one of the determinants of customer loyalty because good relationship marketing will create and maintain customer loyalty. So the higher the relationship marketing applied will increase customer loyalty Keywords: Relationship Marketing and Customer Loyalty